2018
DOI: 10.1007/s00332-017-9438-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromodulation on Excitatory–Inhibitory Neural Network Dynamics Depend on Network Connectivity Structure

Abstract: Acetylcholine (ACh), one of the brain's most potent neuromodulators, can affect intrinsic neuron properties through blockade of an M-type potassium current. The effect of ACh on excitatory and inhibitory cells with this potassium channel modulates their membrane excitability, which in turn affects their tendency to synchronize in networks. Here, we study the resulting changes in dynamics in networks with inter-connected excitatory and inhibitory populations (E-I networks), which are ubiquitous in the brain. Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…The measure used to quantify coherent activity in the simulated networks, here termed a Synchrony Measure, is a slight adaptation of a commonly used measure created by Rinzel, 1993, 1994) that quantifies the degree of spiking coincidence in the network. This particular implementation of this measure has been utilized in previous studies (Rich et al, 2016(Rich et al, , 2017(Rich et al, , 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measure used to quantify coherent activity in the simulated networks, here termed a Synchrony Measure, is a slight adaptation of a commonly used measure created by Rinzel, 1993, 1994) that quantifies the degree of spiking coincidence in the network. This particular implementation of this measure has been utilized in previous studies (Rich et al, 2016(Rich et al, , 2017(Rich et al, , 2018.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the results of Hansel et al (1995) imply that an excitatory network made up of cells of the type studied here is highly unlikely to ever synchronize. Similarly, while the Pyramidal Interneuron Network Gamma (PING) mechanism is commonly cited as a mechanism causing synchronous oscillations in E-I networks (Traub et al, 1997;Ermentrout and Kopell, 1998;Whittington et al, 2000;Kopell et al, 2010), recent work has revealed that the predictions of this mechanism are altered by varying individual cellular properties and network connectivity (Rich et al, 2017(Rich et al, , 2018.…”
Section: The Relationship Between the "Bistable Transition" Mechanismmentioning
confidence: 99%
“…GABA are calculated by Equations (2)-(4). The newly added current I p M is described as follows (Rich et al, 2018)…”
Section: Populations Py and In In The Cortical Modulementioning
confidence: 99%
“…The measure used to quantify coherent activity in the simulated networks, here termed 216 a Synchrony Measure, is a slight adaptation of a commonly used measure created by 217 Golomb and Rinzel [40,41] that quantifies the degree of spiking coincidence in the 218 network. This particular implementation of this measure has been utilized in previous 219 studies [23,42,43] 220 Briefly, the measure involved convolving a Gaussian function with the time of each 221 action potential for every cell to generate functions V i (t). The population averaged 222 voltage V (t) was then defined as…”
mentioning
confidence: 99%
“…[74] imply that an 718 excitatory network made up of cells of the type studied here is highly unlikely to ever 719 synchronize. Similarly, while the Pyramidal Interneuron Network Gamma (PING) 720 mechanism is commonly cited as a mechanism causing synchronous oscillations in E-I 721 networks [16,72,75,76], recent work has revealed that the predictions of this mechanism 722 are altered by varying individual cellular properties and network connectivity [42,43]. consideration.…”
mentioning
confidence: 99%